Pengaruh Earning Per Share dan Return On Equity serta Gross Profit Margin terhadap Harga Saham pada Sub Sektor Rokok yang Terdaftar di Bursa Efek Indonesia - I Komang Agus Triadi; I Nengah Suarmanayasa (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to examine the effect of earning per share, return on equity and gross profit margin simultaneously and partially on stock prices. The research design used is quantitative causal. The population in this study were companies in the cigarette sub sector listed on the Indonesia Stock Exchange, amounting to 4 companies. Data was collected using document recording and then analyzed using multiple linear regression. The results of this study indicate that: (1) earnings per share, dividend payout ratio and return on equity affect stock prices with an effect of 86,5%, (2) earnings per share has a 78,3% positive effect on stock prices, (3) dividend payout ratio has a 64,5% positive effect on stock prices, (4) return on equity has a 72,8% positive effect on stock prices.